(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
The effectiveness of discus throwing is one of the activities of throwing the square and field competitions, and it is one of the individual competitions that needs to implement modern scientific methods through the development of sports training science, which aims to improve the level of players ’physical and skill capabilities through careful planning of the training program for the purpose of developing its efficiency in performing all requirements for the effectiveness of throwing The disk, and the dynamic of the training of training is a structural physical process that depends on the rules and foundations of training in terms of the components of the training pregnancy, and through the researcher’s practice of applying the performance as the researcher is one of the teachers and coaches of the activities of the square and the field in the academic field at Basra University and note that there is a clear decline in the level of performance, especially In performance and achievement among the players of the youth of the Basra Governorate team for the effectiveness, and the researcher assumed that it is due to the weak level of physical performance associated with the skill performance at the archers, and for this it is necessary to legalize exercises on the foundations of the dynamic pregnancy, the size, intensity, and comfort in accurate scientific manner, and the goal of research is to prepare physical effort exercises according to the foundations of pregnancy and comfort In developing the rapid strength of the two men and arms among the players ’effectiveness of discus. For young people, the researcher used the experimental approach to the tribal and post testing of the experimental and control groups, and the research community was identified for the players of the Basra Governorate youth team for the training season 2022/2023, which numbered (10) players, as the research sample was chosen in a comprehensive inventory method and divided the sample into two experimental groups and the control group and with (reality 5) A player for each group, and the physical voltage exercises were applied according to the foundations of pregnancy and rest on the experimental group for an eight -week and by three training units per week and they used the SPSS statistical bag to process data and obtain results, including the researcher to the most important conclusions that physical effort exercises according to dynamic foundations Pregnancy and comfort is a positive impact on developing the rapid strength of the arms and legs of the players of the effectiveness of the discus.